Contemporary Robinsonades in German Literature - Pokrywka, Rafał (Porównania, 2019)
Following the publication of Robinson Crusoe, the Robinsonade genre became part of German literature tradition almost immediately. The contemporary novel in German language refers to the genre or to its characteristic motifs such as eremite in a hermetic (mainly insular) environment or a small group in abnormal social conditions. In the paper three variants of a modern Robinsonade are presented: (1) historical and political narrations that refer to past or contemporary politics critically, predominantly on the basis of postcolonial discourse; (2) postapocalyptic narrations that depict modern Robinsons after a catastrophe, in a future world or in outer space; (3) love stories where an island becomes a place of emotional relationship, utopian isolation and solitude of two lovers.